1998
DOI: 10.1046/j.1365-2222.1998.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–response relationships of occupational inhalative allergens

Abstract: Only a few threshold limit values exist at present for allergens in the workplace known to cause bronchial asthma. This contrasts with the great number of occupational asthma cases observed in industrialized countries. Recently published studies provide clear evidence for exposure intensity response relationships of occupational allergens of plant, microbiological, animal or man-made origin. If allergen exposure levels fall short of determined limit values, they are not associated with an increased risk of occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 70 publications
0
44
0
Order By: Relevance
“…Evidence that sensitization is exposure related exists for many substances, for example isocyanates and enzymes (1). Once sensitized, workers can react to much lower levels of exposure, sometimes below limits of detection.…”
Section: Beryllium As Paradigmmentioning
confidence: 99%
“…Evidence that sensitization is exposure related exists for many substances, for example isocyanates and enzymes (1). Once sensitized, workers can react to much lower levels of exposure, sometimes below limits of detection.…”
Section: Beryllium As Paradigmmentioning
confidence: 99%
“…Studies such as these are costly and time consuming, but they provide evidence of sufficient strength to enable the development of preventive strategies for the most significant causes of OA, including flour, for which acceptable limits of exposure to prevent sensitisation and disease have been proposed [78]. Similar thresholds need to be proposed for other occupational agents [79].…”
Section: Understanding Of Exposure/response Relationships Through Cohmentioning
confidence: 99%
“…However, studies on other occupational allergens have reported that averting or decreasing allergen exposure in the workplace is the most effective approach for preventing asthma (27). Thus, this current lack of data does not obviate the uses of either the HSP and STI assays as a means of monitoring the effectiveness of workplace control measures in reducing exposure to inhalable soya allergens to as low as is reasonably practical.…”
Section: Discussionmentioning
confidence: 97%